THE ROLE OF SOCIAL ENTREPRENEURSHIP THROUGH COOPERATIVE ORGANIZATIONS AS A SOCIO-ECONOMIC SYSTEM - Muhardi Muhardi; Deden Gandana Madjakusumah; Norsiah Hami; Nurdin Nurdin (Univeristas Islam Bandung, 2022)
This study aims to understand the role of social entrepreneurship through cooperative organization as a socio-economic system. The approach used is descriptive qualitative. This study takes a cooperative in the city of Bandung as unit of analysis. There are two types of data used, namely primary and secondary data. The collection technique for primary data is carried out through in-depth interviews with management, cooperative supervisors, and members. Meanwhile, secondary data is obtained from reports on the results of annual member meetings. This study is also enriched with information on the results of community service activities regarding social entrepreneurship. The results of the study show that a well-managed cooperative will provide sustainable socio-economic benefits for its members. Kopsyahmas cooperative as the object of this research not only contributes in providing economic benefits, but also social benefits for its members, even for non-member communities. The role of social entrepreneurship through cooperative organizations includes the establishment and growth of several new micro-entrepreneurs initiated through the distribution of business loans for the community members of the cooperatives. The existence of this cooperative has also reduced the number of people who take up loans from moneylenders. In addition, various social activities have been carried out by this cooperative through compensation and ta'awun for the community in its environment.